Perancangan Aplikasi Evaluasi Pembelajaran Siswa Berbasis Web Menggunakan Framework Codeigniter pada Mata Pelajaran Bahasa Inggris Kelas X di SMKN 1 Gunung Talang Kab Solok - Luthfi, Rahmat; Supriadi, Supriadi; Efriyanti, Liza; Musril, Hari Antoni (Indonesian Research Journal on Education, 2022)
This research is motivated by the implementation of the evaluation of learning in English subjects at SMK N 1 Gunung Talang Kab Solok conventionally using paper that is less efficient so that such an evaluation of learning takes a long time and has implications for being ineffective. The research method used is the Research and Development (R&D) research method, which is a method used to produce a system, the R&D model used is the 4D version, namely, define, design, develop, and disseminate, with the system development model using the System Development Life Cycle (SDLC) by applying the waterfall model consisting of Communication, Planning, Modeling, Construction, and Deployment. The product test used in this study is a validity test by experts, namely program experts, evaluation experts, linguists, practicality tests by English subject teachers and effectiveness tests by students. The results of the author's research are in the form of student learning evaluation applications that can be used by teachers in carrying out student learning evaluations. Based on the results of the research that the researchers did, the researchers succeeded in making a web-based student learning evaluation application product for class X English subjects at SMK N 1 Gunung Talang, SolokRegency. The results of the validity tests conducted by the validators of each field show that this product is valid with a value of 0.78. The results of the practicality test conducted by the English teacher at SMK N 1 Gunung Talang showed that this product was declared practical with a value of 0.66. And the results of the effectiveness test conducted with class X students showed this product was very effective with a value of 0.81.